ANALISIS KESEJAHTERAAN BURUH PELABUHAN SINTETE KABUPATEN SAMBAS - Putri, Nadya Eka; Asriati, Nuraini; Khosmas, Khosmas (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract This research aims to. 1) Knowing the income of the Sintete Port workers. 2) The level of expenditure on Port workers. 3) The state of residence of the Sintete Port workers. 4) Knowing the health insurance in the members of the Sintete Port worker?s family. 5) Ability to send children to school. In this study the author uses a type of qualitative research that is research that produces descriptive data in the form of written or oral words and explain the data through reasonimg based on logic to draw logical conclusions about the data analyzed,so that it can describe the situation systematically in accordance with the phenomenon being researched. Data collection techniques use observation, interview, documentation and triangulation techniques. The results showed that: (1) The income of workers to meet their daily needs was still very lacking (2)The expenditure of port workers was still insufficient (3)The state of the dockers? living quarters could be concluded that they had decent homes. (4) assurance the health of family members of dock workers is guaranteed from the workplace institution. (5) The school fess for children are not sufficient to finance children?s schooling. Keywords: Welfare, Revenue and Expenditures, Port Laborers